PERAN PIMPINAN DALAM KADERISASI CABANG (DPC) PARTAI DEMOKRAT KOTA PEKANBARU - ", Nursal; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The cadre of the Democratic Party Branch Board (DPC) aims to strengthen the party's institution so that the regeneration process must be continuously conducted to strengthen the ties within the Democratic party. Political parties without regeneration will not mean anything. Every political party must have a good regeneration system. A good cadre system is obtained when each related party works together in forming a regeneration pattern. It is therefore necessary for cooperation between the parties who perform the cadre and new members who will join as well as other factors such as materials that form the pattern of thinking and working a cadre in accordance with the goals of the party. This study aims to Know the cadre of the Democratic Party of Pekanbaru City and to know Factors cause cadres moved from other political parties to the democratic party.This study used descriptive qualitative method. Data collection techniques used based on the reality of the field through observation, interviews, and documentation. Informants in this study amounted to 6 people, 3 people as members of the Regional House of Representatives Pekanbaru City and 3 more is the Secretary of DPC Democratic Party of Pekanbaru City and Division who occupy the position at DPC Democratic Party Pekanbaru City. Data analysis technique used is interactive data analysis model. While for examination of data validity of researcher use technique of elongation of participation and also triangulation.Based on the results of research that the cadre conducted in DPC Democratic Party of Pekanbaru City to do that is: the envoy from the Democratic Party went to new members for its readiness and see the wishes of candidates for the battle of elections 2014. And then pengkadaren done in DPC Democratic Party Pekanabru City, Competence , Knowledge, Attitude (Behavior). In addition, it does not escape the attention of the Democratic Party in the determination to be nominated in the election Year 2014 ago sebgaia follows: the popularity of figures, financially.Keyword: Role, Regeneration